2019
DOI: 10.4103/gmit.gmit_72_18
|View full text |Cite
|
Sign up to set email alerts
|

Interventions and quality of life in stress urinary incontinence

Abstract: Introduction:Stress urinary incontinence (SUI), though is more prevalent than many chronic diseases, has remained largely underreported and underdiagnosed condition. We aimed to find the improvement in the quality of life (QoL) of women with SUI after individual interventions, namely mid-urethral sling (MUS), pelvic floor muscle training (PFMT), and no treatment/control group, as primary treatment modalities.Materials and Methods:This was a prospective interventional case–control study conducted at a universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…Its incidence is about 30% in the middle-aged and old. 6 In addition to behavior therapy and pelvic floor muscle exercise, 7 the most commonly used minimally invasive treatment is transvaginal tension-free mid-urethral tape in clinic. Since reported the first case of transvaginal tension-free mid-urethral tape (TVT) in 1996, TVT has been the gold standard for the treatment of various types of urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Its incidence is about 30% in the middle-aged and old. 6 In addition to behavior therapy and pelvic floor muscle exercise, 7 the most commonly used minimally invasive treatment is transvaginal tension-free mid-urethral tape in clinic. Since reported the first case of transvaginal tension-free mid-urethral tape (TVT) in 1996, TVT has been the gold standard for the treatment of various types of urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SUI depends on its definition, and several previous studies have reported that approximately 23.8–40.8% of Korean women are affected [ 3 , 4 ]. SUI not only decreases the quality of life, leading to depression and social isolation if severe [ 5 ], but also has financial and social costs.…”
Section: Introductionmentioning
confidence: 99%
“…Stress urinary incontinence (SUI) is a prevalent disorder that is characterized by leakage of urine after physical stress [ 1 ]. Surgical procedures are widely performed for women with failed conservative management or women seeking definitive treatment [ 2 ]. Mid-urethral sling (MUS) is a highly effective, minimally-invasive, surgical approach for SUI that is based on the passing of a small band of a synthetic mesh into either the retropubic space (known as tension-free vaginal tape, TVT) or through the obturator foramen (known as trans-obturator tape, TOT or TVT-O, through the inside-out route) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%